Effects of seasonal variation on microbial community and flavor of strong-flavor Baijiu Daqu from different regions - YU Lin, DU Gang, ZHONG Ciping, LI Jing, HE Yuan, CHEN Youjun, WU Huaxing, CHEN Xueqiang (Zhongguo niangzao)
To investigate the influences of seasonal variation on the microbial community structure and flavor compounds of strong-flavor (Nongxiang- xing) Baijiu Daqu in Qionglai and Yibin, the microbial communities were analyzed by Illumina Miseq high-throughput sequencing technology, and the volatile flavor compounds were analyzed by headspace-tandem thermal desorptionin (HS-TD) combined with gas chromatography-tandem quadrupole time-of-flight mass spectrometry (GC-QTOF MS). The differential volatile flavor compounds were analyzed based on variable importance projection (VIP) value (VIP>0.5), and the correlation between microbial community structure and volatile flavor compounds was also analyzed. The results showed that the relative abundance of Lactobacillus in Daqu from Qionglai and Yibin was the highest in summer (31.1% and 31.4%, respectively). The relative abundances of Aspergillus, Fusarium and Talaromyces were higher in spring and autumn, respectively. A total of 35 volatile flavor compounds were detected in Qionglai and Yibin Daqu, common and unique volatile flavor compounds were 24, 4 and 7, respectively. The substances with relatively high contents were alcohols (40.64%) and aldehydes (34.52%), respectively. The differential volatile flavor compounds of Daqu from Qionglai and Yibin included 13 kinds, such as isovaleraldehyde, 2,3-butanediol, 3-hydroxy-2-butanone, etc. Bacillus and etc. in Daqu from Qionglai showed significant positive correlation with ethyl acetate, 2,3-butanedione and 2,5-dimethylpyrazine, which contributed significantly to the production of ester, alcohol, etc.